The Influence of Sheikh Galib in Poems of Seref Hanım: In the Context of the Poem with “Eylerdi Yar” Redif - Kuzu, Fettah (Fırat University, 2024)
Seref Hanım was one of the poets trying to compose poems adhesion to tradition in a period that classical Turkish poetry began to give its place to Western style poetry. Despite her being a woman and women’s limited facilities in social life, she has been a poet who has succeeded to improve herself, internalized classical Turkish poetry tradition and gained accomplishment in handling classical poetic material concordantly in her poems. In her Divan, poems written in different poetic forms of classical poetry, success of using the materials of Turkish classical poetry like symbols, figures of speech, metaphorical statements, thematic constructions and mastery on subjects treated in these poems provide significant traces about her literery personality. However, problems related to her being a woman have reflected to her art negatively. An obvious influence of Sheikh Galib has been seen especially in her ghazals written with rhymes and redifs same as those of Galib’s poems. Seref Hanım who has been affiliated to Mawlawiyya, was born after the death of Sheikh Galib and gained inspiration from him who has got a rightful reputation and been also a Mawlawi sheikh. As can be understood from her poems Seref Hanım has been a hihgly educated, as a woman well-qualified and intellectual poet of her period. In this study, the influence of Galib on Seref Hanım is tried to be analysed in the sample of ghazals with “eylerdi yar” redif and similar verses from different poems of both poets.

Klasik Türk şiirine rağbetin, yerini Batı tarzı şiire bırakmaya başladığı bir dönemde geleneğe bağlı eser verme gayretinde olan şairlerden biri de Şeref Hanım’dır. 19. yüzyıl Osmanlı toplumunda, özellikle dönemin bir kadın için sosyal hayatta kısıtlı sayılabilecek imkânlarına rağmen Şeref Hanım kendini yetiştirebilmiş, klasik şiir geleneğini özümsemiş ve eserlerinde klasik şiir malzemesini kurallarına uygun biçimde işleyebilmiş bir sanatkârdır. Şairin, Dîvânı’nda farklı nazım şekilleriyle kaleme almış olduğu şiirleri, bu şiirlerdeki semboller, edebî sanatlar ve mazmunları kullanmadaki başarısı, şiirlerin tematik kurgusu ve işlenen konulara hâkimiyeti, onun edebî kişiliği hakkında önemli ipuçları sunmaktadır. Ancak onun özellikle bir kadın olmasından kaynaklı zorluklar, sanatına da olumsuz yansımıştır. Şeref Hanım’ın, özellikle aynı kafiye ve redif seçimiyle kaleme aldığı gazellerinde açık bir Şeyh Gâlib etkisi görülmektedir. Kendisi Mevlevî olan Şeref Hanım, Şeyh Gâlib’in vefatından kısa bir zaman sonra dünyaya gelmiş, onun Türk şiirindeki şöhretinden etkilenmiş ve onun bir Mevlevî şeyhi olmasından dolayı kendi edebî gelişiminde ondan ilham almıştır. Şiirlerinden anlaşılacağı üzere Şeref Hanım iyi eğitim almış, bir kadın olarak dönemi için kendini iyi yetiştirmiş entelektüel bir şairdir. Bu çalışmada Şeref Hanım’ın, “eylerdi yâr” redifli gazeli örneğinde aynı redifli bir gazeli bulunan Şeyh Gâlib’den ne ölçüde etkilenmiş olduğu, iki şairin farklı şiirlerinden benzer beyitlerin de incelenmesiyle ortaya konmaya çalışılacaktır.
ŞEREF HANIM’IN ŞİİRLERİNDE ŞEYH GÂLİB ETKİSİ: “EYLERDİ YÂR” REDİFLİ GAZELİ BAĞLAMINDA
Keywords: Turkish Islamic Literature; Türk İslam Edebiyatı